The Correlation of Students’ Vocabulary Mastery and Translation Accuracy in Narrative Text - Nurfadhila, Putri; Intan, Nur; Sitti Maryam Hamid; Ratu Yulianti Natsir (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The aim of this research is to examine the extent to which students' vocabulary mastery is related to the accuracy of their translation in the narrative text "The Legend of Roro Jonggrang" in Indonesian. The research was conducted using a quantitative research design with correlational methods. The data was obtained from a questionnaire which was created via Google Forms and distributed online via the WhatsApp application. With a significance value (p-value) of 0.000, which is less than the cutoff of 0.05, the results showed a significant link between vocabulary and translation accuracy. The findings of the study have a big impact on language instruction, especially when it comes to teaching English in Indonesia. Educators should prioritize vocabulary development to enhance students' translation skills and overall language proficiency.